Propuesta de un procedimiento para el proceso de planificación del inventario en el hotel Herradura - Dickinson González, Yoaima (2009)
Today, like years ago, Cuba is involved in a continuous struggle to improve the economy in its numerous sectors withspecific emphasis in tourism industry, which has globally evolved as one of the most increasing phenomena. Cuba,not being exerted from that situation, has placed it as the engine of the economy based on a previous redirection of itseconomic strategy. For this reason, it is necessary to search new managerial alternatives and theories contributing to thisdevelopment. In particular, finance management catches a great attention as a function of enterprise administration, asit is in charge of managing the productive resources in such a way that the organization meets the expected economicand financial results: more efficiency, less risk involved and higher profitability. This important function affects considerablydecision making process in terms of: maintaining appropriate cash flow levels, types of terms of credit to offerto clients or cost-effective inventory levels. All these arguments have led to the main purpose of this investigation andthat is to propose a procedure for inventory planning in hotelier organizations.